ALISHER NAVOI'S IMAGINATION SKILLS (Archive of Conferences, 2020)
Tasbih is a kind of art that occurs in the artistic creation of every nation. Navoi's allegories are distinguished by their uniqueness. That is why a person who begins to study the lyrical heritage of the poet does not go without mentioning the metaphors in the heritage of the poet. This article analyzes the beautiful allusions to the image of the mistress in the ghazals of Alisher Navoi